2016
DOI: 10.1016/j.jveb.2016.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic determination of noise reactivity in 3 breeds of working dogs: A cautionary tale of age, breed, behavioral assessment, and genetics

Abstract: Noise reactivity is a common problem for dogs, and may progress to true phobia. Survey studies report that some type of noise reaction occurs in up to half of all pet dogs throughout their lifetimes, indicating that noise reactivity/phobia is a welfare issue. Familial aggregations of affected dogs have been reported and increased prevalence in certain breeds has been suggested. Reactivity to noise can severely compromise function in both pet and working dogs. Noise reactivity may be co-morbid with many anxiety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 91 publications
2
41
1
Order By: Relevance
“…Approximately 14%-20% of dog patients [18,19] from general veterinary practices show signs of SRP in their owners' absence [20], and the anxiety emotional system is recognized as one possible cause. However, as with other anxiety disorders in veterinary patients, underdiagnosis of anxiety-dependent separation problems has been previously reported [21] due to misinterpretation of normal and pathological anxiety [22] and the lack of recognition of mild clinical signs by owners [23]. Therefore, unsurprisingly, according to Karagiannis et al [24], it is suspected that up to 50%-56% of the overall dog population may actually display clinical symptoms of SRP at some point in their life [25,26], which, out of the total population of approximately 160 million dogs in the US and Europe [27,28] represents approximately 85 million dogs with SRP on the two continents.…”
Section: Introductionmentioning
confidence: 85%
“…Approximately 14%-20% of dog patients [18,19] from general veterinary practices show signs of SRP in their owners' absence [20], and the anxiety emotional system is recognized as one possible cause. However, as with other anxiety disorders in veterinary patients, underdiagnosis of anxiety-dependent separation problems has been previously reported [21] due to misinterpretation of normal and pathological anxiety [22] and the lack of recognition of mild clinical signs by owners [23]. Therefore, unsurprisingly, according to Karagiannis et al [24], it is suspected that up to 50%-56% of the overall dog population may actually display clinical symptoms of SRP at some point in their life [25,26], which, out of the total population of approximately 160 million dogs in the US and Europe [27,28] represents approximately 85 million dogs with SRP on the two continents.…”
Section: Introductionmentioning
confidence: 85%
“…Thus, fear of firework, gunshots and thunder does not necessarily seem to coincide with sensitivity to other types of noises. As in (2), no relationship with separation related problems was detected, although some other studies confirmed Overall et al’s (12,29) notion that noise fears and separation related problems frequently co-occur (1,3). In my sample, no other behavioural problems were associated with firework fears, indicating that noise fears are a separate phenotype from social fears (dogs/ humans), and are also unrelated to other behaviour problems including resource guarding and hyperactivity.…”
Section: Discussionmentioning
confidence: 57%
“…Fireworks appear to be the most common trigger of noise fears in dogs, although the great majority of affected dogs concomitantly show fears of gunshots and thunderstorms (1,2,12). Breed or breed group has consistently been identified as being associated with different susceptibility to firework fears (13,12), pointing to contributing genetic factors. While the observed breed differences in noise fears are likely polygenic (12), a few genes contributing to noise fears in some breeds have recently been identified (15,16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering their high prevalence, these anxiety disorders are chronically under-diagnosed and under-treated in people (Kimiskidis and Valeta, 2012;Thomé-Souza et al, 2007). Underdiagnosis of anxiety disorders in veterinary patients has been extensively described (Overall et al, 2016). Misinterpretation of normal and pathological anxiety (Tami and Gallagher, 2009) and lack of recognition of mild clinical signs by owners (Mariti et al, 2012) are likely to contribute to the under reporting of comorbid anxiety disorders in veterinary species.…”
Section: Anxiety Disorder Comorbid To Epilepsy In Peoplementioning
confidence: 99%